2022
DOI: 10.1111/pce.14402
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive expression of JASMONATE RESISTANT 1 induces molecular changes that prime the plants to better withstand drought

Abstract: In this study, we investigated Arabidopsis thaliana plants with altered levels of the enzyme JASMONATE RESISTANT 1 (JAR1), which converts jasmonic acid (JA) to jasmonoyl-L-isoleucine (JA-Ile). Analysis of a newly generated overexpression line (35S::JAR1) revealed that constitutively increased JA-Ile production in 35S::JAR1 alters plant development, resulting in stunted growth and delayed flowering. Under droughtstress conditions, 35S::JAR1 plants showed reduced wilting and recovered better from desiccation tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 64 publications
0
14
1
Order By: Relevance
“…JAR1 is a well characterized aminotransferase competent for this reaction [9]. The level of JAR1 expression has recently been shown to affect drought resistance [57] and a double cat2 jar1 mutant presented an enhanced lesion phenotype compared to cat2 [29]. However, no consistent up-regulation of this gene was observed in our experiments.…”
Section: Ja Inactivation During Oxidative Stresscontrasting
confidence: 64%
“…JAR1 is a well characterized aminotransferase competent for this reaction [9]. The level of JAR1 expression has recently been shown to affect drought resistance [57] and a double cat2 jar1 mutant presented an enhanced lesion phenotype compared to cat2 [29]. However, no consistent up-regulation of this gene was observed in our experiments.…”
Section: Ja Inactivation During Oxidative Stresscontrasting
confidence: 64%
“…Among these candidates, two genes, AtERF96 and AtJAR1 , are annotated to be involved in flower development. AtJAR1 was reported to alter plant development, causing stunted growth and delayed flowering (Mahmud et al, 2022). AtERF96 belongs to the AP2/ERF gene family, which is involved in modulating gynoecium development (Durán‐Medina et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The ratio JA‐Ile/JA also increased in water‐stressed petioles, thus suggesting an activation of the enzyme JAR1 and that the metabolic pathway of jasmonates was probably directed towards the formation of JA‐Ile (Staswick & Tiryaki, 2004; Wasternack & Hause, 2013). It has been previously shown that exposure to drought induces jasmonate biosynthesis in various species (de Ollas et al, 2015), and a recent study suggested a drought stress tolerance priming effect of jasmonates via JAR‐1 mediated accumulation of JA‐Ile in Arabidopsis (Mahmud et al, 2022). Therefore, it appears that jasmonates, and more specifically the bioactive form JA‐Ile, play a major role in drought stress tolerance, particularly in conditioning the tissue (petiole 2) containing the AZ for leaf abscission induced by mechanical stress to occur.…”
Section: Discussionmentioning
confidence: 99%
“…shown that exposure to drought induces jasmonate biosynthesis in various species (de Ollas et al, 2015), and a recent study suggested a drought stress tolerance priming effect of jasmonates via JAR-1 mediated accumulation of JA-Ile in Arabidopsis (Mahmud et al, 2022).…”
Section: Irrigatedmentioning
confidence: 97%